Fusobacterium nucleatum bacteremia with pneumopathy in a patient receiving eculizumab: A case report. (February 2020) - Seibel, Jean; Rebibou, Jean-Michel; Bonnot, Pierre-Henri; Bernard, Anna; Zanetta, Gilbert; Tetu, Jennifer; Legendre, Mathieu
Abstract: Fusobacterium nucleatum is a common oral commensal bacterium capable of severe invasive infections. We report a case of a diffuse bilateral pneumopathy with F. nucleatum -positive blood culture successfully treated by common antibiotics in a patient receiving eculizumab for a drug-induced thrombotic microangiopathy (TMA). It is the first described case of a severe F. nucleatum -associated infection in a patient undergoing terminal complement inhibitor therapy. We suggest providing preventive dental care before eculizumab initiation. Highlights: The field of application of eculizumab is currently spreading. The pathogeny of Fusobacterium nucleatum depends on complement pathway activation. Such a severe complication could be prevented by simple means.